The Enhanced liver fibrosis score is associated with clinical outcomes and disease progression in patients with chronic liver disease. (28th August 2015) - Irvine, Katharine M.; Wockner, Leesa F.; Shanker, Mihir; Fagan, Kevin J.; Horsfall, Leigh U.; Fletcher, Linda M.; Ungerer, Jacobus P. J.; Pretorius, Carel J.; Miller, Gregory C.; Clouston, Andrew D.; Lampe, Guy; Powell, Elizabeth E.
Abstract: Background and Aims: Current tools for risk stratification of chronic liver disease subjects are limited. We aimed to determine whether the serum‐based ELF (Enhanced Liver Fibrosis) test predicted liver‐related clinical outcomes, or progression to advanced liver disease, and to compare the performance of ELF to liver biopsy and non‐invasive algorithms. Methods: Three hundred patients with ELF scores assayed at the time of liver biopsy were followed up (median 6.1 years) for liver‐related clinical outcomes ( n = 16) and clear evidence of progression to advanced fibrosis ( n = 18), by review of medical records and clinical data. Results: Fourteen of 73 (19.2%) patients with ELF score indicative of advanced fibrosis (≥9.8, the manufacturer's cut‐off) had a liver‐related clinical outcome, compared to only two of 227 (<1%) patients with ELF score <9.8. In contrast, the simple scores APRI and FIB‐4 would only have predicted subsequent decompensation in six and four patients respectively. A unit increase in ELF score was associated with a 2.53‐fold increased risk of a liver‐related event (adjusted for age and stage of fibrosis). In patients without advanced fibrosis on biopsy at recruitment, 55% (10/18) with an ELF score ≥9.8 showed clear evidence of progression to advanced fibrosis (after an average 6 years), whereas only 3.5% of those with an ELF score <9.8 (8/207) progressed (average 14 years). In these subjects, a unit increase in ELF score was associated with a 4.34‐fold increased risk of progression. Conclusions: The ELF score is a valuable tool for risk stratification of patients with chronic liver disease.